1995
DOI: 10.1093/intimm/7.4.645
|View full text |Cite
|
Sign up to set email alerts
|

The perinatal presence of antigen (p-azophenylarsonate) or anti-μ antibodies lead to the loss of the recurrent idiotype (CRIA) in A/J mice

Abstract: The immune response of A/J mice against p-azophenylarsonate (Ars)-keyhole limpet hemocyanin (KLH) is characterized by the dominance, late in primary and during the secondary, of a recurrent idiotype called CRIA, encoded by a canonical combination of Ig gene segments. In this study, A/J mice were given Ars coupled to deaggregated human gamma globulins (dHGG) within 24 h after delivery. The offsprings from these mice were then exposed as adults to Ars-KLH. These animals developed an unusual immune response. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This would suggest that affinity alone cannot dictate dominance. In agreement our data suggest that idiotype dominance can be easily broken by various means, while the level of anti-arsonate antibodies is usually not affected [13][14][15][16].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This would suggest that affinity alone cannot dictate dominance. In agreement our data suggest that idiotype dominance can be easily broken by various means, while the level of anti-arsonate antibodies is usually not affected [13][14][15][16].…”
Section: Introductionsupporting
confidence: 89%
“…The inactivation of autoanti-idiotypic precursor B cells in neonates [15] as well as the treatment at birth with antigen or anti-? antibodies [14] lead to the loss of CRI-A dominance, while the levels of anti-arsonate antibodies are normal.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that anti-Id antibodies can be generated by the neonate in response to maternal IgG ( 180 ) or acquired from the mother ( 179 ). Several studies have demonstrated the ability of endogenous and maternally-delivered anti-Id antibodies to modify the B lymphocyte repertoire in neonatal mice, often resulting in suppression of the targeted B lymphocyte ( 181 183 ). Furthermore, there is evidence that T cell receptors (TCR) may also be a target for anti-Id antibody suppression in neonatal mice, resulting in early shaping of the T lymphocyte repertoire ( 184 ) ( Figure 3 ).…”
Section: Maternal Antibodies In Immune Developmentmentioning
confidence: 99%
“…In such systems, the suppression of antibody responses was always reversible. Its recovery was associated with the expression of the same (151) or different idiotypic repertoires (152)(153)(154). For instance, the transfer of maternal anti-idiotypic IgGs directed against anti-phosphorylcholine (PC) antibodies skewed the repertoires of PC-specific B lymphocytes after immunization of the offspring with PC later in life (155).…”
Section: Shaping Of Adaptive Immune Repertoires By Maternal Iggmentioning
confidence: 99%